Genome-Wide Association Study for Idiopathic Ventricular Tachyarrhythmias Identifies Key Role of CCR7 and PKN2 in Calcium Homeostasis and Cardiac Rhythm Maintenance. (27th July 2022) - Fang, Chen; Wang, Pengxia; Yu, Dong; Zhang, Xiaoyu; Gou, Dongzhi; Liang, Lina; Bai, Xuemei; Xie, Wen; Li, Hui; Pu, Jielin; Yao, Yufeng; Wang, Binbin; et al.
Abstract : Background: Idiopathic ventricular tachycardia (VT) occurs in structurally normal hearts and accounts for a significant number of all types of VT. The genome-wide association study is the most effective strategy for identifying novel genetic variants for common diseases. However, no genome-wide association study has been reported for idiopathic VT. Methods: We conducted the first genome-wide association study for idiopathic VT in the Chinese Han population using a discovery population with 246 cases and 648 controls and a replication population with 222 cases and >4072 controls. Candidate VT genes were functionally characterized in zebrafish. Real-time RT-PCR analysis was used to determine the effects of candidate genes on expression of ion channels and regulators. Patch-clamping was used to record L-type calcium current from neonatal rat cardiomyocytes with overexpression of candidate genes. Results: We identified 4 significant loci represented by rs78960694 (minor allele frequency [MAF]=5.02% in cases and 1.84% in controls; P =4.30×10 − 12, odds ratio [OR]=3.91) and rs2229095 (MAF=3.25% in cases and 1.63% in controls; P =1.02×10 − 7, OR=3.44) near and in CCR7, respectively, rs68126098 in NELL1 (MAF=40.98% in cases and 32.07% in controls; P= 2.40×10 − 8, OR=1.53), rs2390325 between PKN2 and LMO4 (MAF=21.19% in cases and 15.12% in controls; P =1.92×10 − 7, OR=1.62), and rs270065 in CSMD1 (MAF=33.63% in cases and 40.25% in controls; P =9.51×10 − 7, OR=0.69). Note that the associations of idiopathic VT for CCR7 variant rs78960694 and NELL1 variant rs68126098 reach genome-wide significance ( P <5.00×10 − 8). Overexpression of either PKN2 or CCR7 increased the heart rate in zebrafish, and enhanced expression of CACNA1C, RYR2, or NOS1AP in zebrafish embryos, HEK293, and AC16 cardiomyocytes. Overexpression of either PKN2 or CCR7 significantly increased L-type Ca2+ current density. Conclusions: The first genome-wide association study identifies 4 novel loci and 2 risk genes ( PKN2 and CCR7 ) for idiopathic VT. These findings identify new molecular determinants for cardiac calcium homeostasis and rhythm maintenance and provide novel targets for diagnosis and treatment for idiopathic VT.